2012
DOI: 10.1097/hjh.0b013e32834f6b2b
|View full text |Cite
|
Sign up to set email alerts
|

Postsystolic strain index is associated with delayed diastolic lengthening and diastolic dysfunction of the left ventricle in untreated hypertension

Abstract: Increased PSI was associated with increased procollagen type I carboxyterminal propeptide and diastolic dysfunction in hypertension. Postsystolic shortening was associated with delayed diastolic lengthening which contributed to diastolic dysfunction in hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…In the present study, the post‐systolic index showed peaks—indicating increased relative myocardial activity delay—in the baso‐septal portion, where longitudinal displacement is higher and longitudinal strain low. This is coincident with the findings of Tsai et al They suggested that an increased post‐systolic index was associated with an accumulation of procollagen type I carboxyterminal propeptide and diastolic dysfunction. Therefore, values in healthy LV myocardium should generally be expected to be low.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the post‐systolic index showed peaks—indicating increased relative myocardial activity delay—in the baso‐septal portion, where longitudinal displacement is higher and longitudinal strain low. This is coincident with the findings of Tsai et al They suggested that an increased post‐systolic index was associated with an accumulation of procollagen type I carboxyterminal propeptide and diastolic dysfunction. Therefore, values in healthy LV myocardium should generally be expected to be low.…”
Section: Discussionsupporting
confidence: 90%
“…Postsystolic shortening (PSS) is a myocardial contraction occurring after the end of ventricular ejection . Although PSS is commonly observed under condition of myocardial ischemia, it can also be detected in nonischemic etiologies, including those associated with diabetes, chronic kidney disease, and hypertension . One of the pathophysiological implications involving PSS is thought to be impinging on diastolic event .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, left ventricular (LV) diastolic function can be influenced by loading conditions, and also several factors may exist outside PSS that relates to diastolic function such as global and regional systolic function, chamber geometry, and even the use of antihypertensive drugs prescribed. Little is known, however, about PSS accounting for LV diastolic dysfunction in terms of the potentially interrelated factors in hypertensive patients …”
Section: Introductionmentioning
confidence: 99%
“…In a study of adults with untreated hypertension, the degree of PSS relative to the end-systolic strain (calculated as postsystolic strain index) was associated with increased procollagen fibers and delayed diastolic lengthening which contribute to diastolic dysfunction. 20 However, these patients still had normal left ventricular longitudinal strain. Whether PSS, in the presence of normal left ventricular longitudinal strain, is an earlier sign of myocardial dysfunction in fetuses with FGR is not yet clear.…”
Section: Circ Cardiovasc Imagingmentioning
confidence: 89%